"When you're coming from the reserve you're not supposed to make it": Stories of Aboriginal athletes pursuing sport and academic careers in "mainstream" cultural contexts. (November 2015) - Blodgett, Amy T.; Schinke, Robert J.
Abstract: Objectives: This project responds to the call for athletic career development and transitions research that centralizes the constitutive role of culture in athletes' experiences (Stambulova & Alfermann, 2009; Stambulova & Ryba, 2014). Within, we explore the cultural transitions of Aboriginal hockey players (14–22 years old) relocated into "mainstream" (Euro-Canadian) cultural contexts to pursue dual careers as students and athletes. Design: The research was framed as a cultural sport psychology initiative. The project was rooted in a local Indigenous decolonizing methodology, which was brought forward via a participatory action research approach. Methods: Mandala drawings and conversational interviews were employed as open-ended data collection processes that enabled the participants to share their stories and meanings through their own cultural perspectives. Vignettes were then used to present their accounts. Results: The participants' careers as athletes and students were precariously navigated within larger cultural tensions to: (a) deal with a loss of belonging in the Aboriginal community; (b) break down negative stereotypes and attitudes that Aboriginal people are not able to "make it"; and (c) give back to the Aboriginal communities they relocated away from. Conclusions: Through a culturally resonant mode of knowledge production, the research uncovers contextual understandings of the cultural transitions experienced by Aboriginal athletes, revealing how this transition intersects with and shapes their dual careers. The project offers insight into the central role of culture in shaping athletes' dual careers, and provides impetus for more idiosyncratic approaches to be adopted in future research. Highlights: Explores cultural transitions of relocated Aboriginal student-athletes. Dealing with a loss of belonging in the Aboriginal community. Emphasis on breaking down negative cultural stereotypes and attitudes. Careers shifted around desire to give back to Aboriginal community. Project contributes to the cultural praxis of athletes' careers.